Ergasiophytes of the Ukrainian flora - Protopopova, Vira V.; Shevera, Myroslav V. (Biodiversity: Research and Conservation, 2015)
The results of an investigation of the ergasiophytes (species deliberately introduced to a region for cultivation) of the Ukraine (458 species) are presented. The systematic, life forms and morphological types of plants with respect to soil moisture spectras, origin and degree of naturalisation of species of thіs group are analyzed. A annotated list of ergasiophytes is provided